Modelling customer demand in forest products industry supply chains: a review of the literature. (13th October 2010) - Vahid, Saba; Maness, Thomas
To remain competitive in today's business environment, forest products manufacturing enterprises can greatly benefit from the concept of Supply Chain Management (SCM). Modelling the supply chain is the first step towards this goal. Since all business activities in a supply chain are carried out to satisfy the end-customer's demand, it is vital to correctly model the demand for the final products or services. This paper provides a review and classification of existing approaches for modelling the end-customer demand in supply chains. It then identifies the promising approaches for use in the context of forest products industry.